Introduction to organic chemistry - Brown, William Henry
This book enables readers to see the connections in organic chemistry and understand the logic: Reaction mechanisms are grouped together to reflect logical relationships, Discusses organic chemistry as it is applied to real-world compounds and problems, Electrostatic potential plots are added throughout the text to enhance the recognition and importance of molecular polarity, Presents problems in a new Looking-Ahead